The catena to James: reading the Letter of James in the Ancient Greek commentary tradition - Albl, Martin C. (Text and editions for New Testament study, 2024)
"The Catena to James (compiled ca. 700 CE) collected excerpts from the best ancient Greek commentaries on the Letter of James, ranging from Origen to Maximus the Confessor. This translation and commentary make the whole Catena available for the first time in a modern language. An extensive introduction locates the Catena both in its own historical and literary context and in the context of modern catena studies. The detailed commentary elucidates the wide-ranging and sophisticated nature of the philological, historical-critical, rhetorical, ethical, theological, and pastoral insights of these ancient readers of James"--